IMPLEMENTASI KEBIJAKAN PEMENUHAN HAK-HAK PENYANDANG DISABILITAS BIDANG KESEAHTERAAN SOSIAL (JAMINAN SOSIAL) DI KABUPATEN GUNUNGKIDUL TAHUN 2018 - Adila Puspa Hestiantini; Ulung Pribadi (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
The problem in this study is the level of satisfaction of people with disabilities in receiving social security assistance from the government. The purpose of this study is to see and analyze which fulfillment of disability rights in social welfare including social security that has been fulfilled. This has an important meaning with public service policies as a form of community welfare related to disability. Supporting the implementation of policies on the fulfillment of the right of persons with disabilities including social security and analyzing comprehensively the implementation of policies on fulfilling the right of persons with disabilities, resources, resources, communication, resources, and dispositions to assist in the matter of social demand problems. In the variables of this study have a significant and not significant relationship. The reason is that this study uses the type of Smart-PLS quantitative research and qualitative interview responses (mixed methodology). The results showed that 4 variables were not significant in implementing the policy on fulfilling the right to disability that contained social security.